Stability of the coal seam roof during the sudden collapse of lateral rocks - Podkopaiev, S; Iordanov, I; Chepiha, D (National Mining University, 2017)
Purpose. To study the effect of dangerous manifestations of rock pressure (in the form of sudden lateral rock collapse) on the state of the coal seam roof developed in difficult mining and geological conditions by various methods of controlling mining pressure and protecting workings. Methods. Analytical studies were carried out using the basic principles of the theories of elasticity, classical mechanics, and oscillations. The roof rocks were presented in the form of a beam whose free end has different versions of support. Findings. As a result of the conducted studies, it was established that in the case of caving in the stratified rock strata, in order to preserve mine workings in the operational state, roof rocks should rest either on filling mass or yielding supports. This will reduce rigidity of the given system and the magnitude of the acting force during the strike of stratified rocks on the beam, due to the increase in the time interval between the application of this force and the maximum deflection of the roof rocks of the developed seam. Originality. To determine the stress state of the immediate roof rocks of the developed coal seam, it is necessary to take into account rigidity of the system under consideration. The rigidity value is determined not only by the static deflection of the structure (beam), but also by the yielding capacity of the support under consideration. Practical implications. The proposed approach to predicting stability of mine workings will contribute to the creation of safe working conditions during mining operations in complex mining and geological conditions, including sudden collapses of lateral rocks.

Цель. Изучение влияния опасных проявлений горного давления, в виде внезапных обрушений боковых пород, на состояние кровли разрабатываемого угольного пласта при различных способах управления горным давлением и охраны выработок в сложных горно-геологических условиях. Методика. Для достижения поставленной цели были выполнены аналитические исследования с привлечением основных положений теории упругости, классической механики и теории колебаний, когда в рассматриваемой системе породы кровли представлены в виде балки, свободный конец которой имеет различные варианты опирания. Результаты. В результате выполненных исследований было установлено, что при обрушениях расслоившейся породной толщи для сохранения горных выработок в эксплуатационном состоянии, породы кровли должны опираться на закладочный массив или податливые опоры. Это позволит уменьшить жесткость рассматриваемой системы, а значит и величину действующей силы при ударе расслоившихся пород о балку, за счет увеличения промежутка времени между моментом приложения этой силы и достижением максимального прогиба пород кровли разрабатываемого пласта. Научная новизна. Для определения напряженно-деформированного состояния пород непосредственной кровли разрабатываемого угольного пласта, необходимо учитывать жесткость рассматриваемой системы, величина которой определяется не только статическим прогибом конструкции (балки), но и учитывает податливость опоры, на которую опирается рассматриваемая конструкция. Практическая значимость. Предложенный подход в прогнозировании устойчивости пород кровли и горных выработок будет способствовать созданию безопасных условий труда при ведении горных работ в сложных горно-геологических условиях, в т.ч. при внезапных обрушениях боковых пород.

Мета. Вивчення впливу небезпечних проявів гірничого тиску у вигляді раптових обвалень бічних порід, на стан покрівлі розроблювального вугільного пласта при різних способах управління гірничим тиском і охорони виробок в складних гірничо-геологічних умовах. Методика. Для досягнення поставленої мети були виконані аналітичні дослідження з залученням основних положень теорії пружності, класичної механіки і теорії коливань, коли в даній системі породи покрівлі представлені у вигляді балки, вільний кінець якої має різні варіанти обпирання. Результати. В результаті виконаних досліджень було встановлено, що при обваленнях розшарованої породної товщі для збереження гірничих виробок в експлуатаційному стані, породи покрівлі повинні спиратися на закладний масив або податливі опори. Це дозволить зменшити жорсткість даної системи, а значить і величину ударної сили при обваленні розшарованих порід на балку, за рахунок збільшення проміжку часу між моментом докладання цієї сили і досягненням максимального прогину порід покрівлі пласта. Наукова новизна. Для визначення напружено-деформованого стану порід безпосередньої покрівлі вугільного пласта, що розробляється, необхідно враховувати жорсткість даної системи, величина якої визначається не тільки статичним прогином конструкції (балки), а й враховує податливість опори, на яку спирається розглянута конструкція. Практична значимість. Запропонований підхід в прогнозуванні стійкості порід покрівлі гірничих виробок сприятиме створенню безпечних умов праці при веденні гірничих робіт в складних гірничо-геологічних умовах, в т.ч. при раптових обваленнях бічних порід.
Keywords: rock pressure; dynamic load; rockburst; fluctuations; rock lamination; goaf stowing